The handbook of discourse analysis - Tannen, Deborah; Hamilton, Heidi Ehernberger; Schiffrin, Deborah (Malden, MA ; Chichester, West Sussex : Wiley Blackwell, 2015)
The second edition of the highly successful Handbook of Discourse Analysis has been expanded and thoroughly updated to reflect the very latest research to have developed since the original publication, including new theoretical paradigms and discourse-analytic models, in an authoritative two-volume set. Twenty new chapters highlight emerging trends and the latest areas of research Contributions reflect the range, depth, and richness of current research in the field Chapters are written by internationally-recognized leaders in their respective fields, constituting a Who's Who of Discourse An.
1.2 Differences between canned and conversational joking2 The Functionalist Phase; 3 Corpus-Based Synthesis; 3.1 Humor styles; 3.2 The Language in the Workplace Project corpus studies; 3.3 Humor support; 3.4 Other corpus-based studies; 3.5 Timing and the prosody of humor; 4 Paradigmatic Shifts in the Study of Humorous Discourse; 4.1 Discourse analysis and cognitivist approaches; 4.2 The multi-functionality of humor; 4.3 The co-construction of humor; 4.4 Finding the boundaries of humor; 4.5 Identification of humor; 4.6 Failed humor; 5 Conclusion; REFERENCES
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Discourse analysis -- Handbooks, manuals, etc; Discourse analysis; LANGUAGE ARTS & DISCIPLINES / General; Communication; Discourse analysis -- Handbooks, manuals, etc; Discourse analysis; Language and culture; Handbooks and manuals; Electronic books; Electronic books